SISTEM INFORMASI PENJADWALAN LABORATORIUM DI SMK MUHAMMADIYAH-9 MEDAN BERBASIS WEB - Donda Sari Tiur Maida Situmorang; Junika Napitupulu; Rimbun Siringoringo (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Information system is a system made by humans consisting of components in the organization to achieve a goal that is to present information. In this study I created a laboratory system scheduling information system. The web is a page that is displayed on the internet that contains certain information (specifically). PHP programing language is a programing language for creating web that is server-side scripting. MySQL is a database server program that is capable of receiving and sending data very quickly, multi-user and using the standard sql (structured query language) command.